Profile of Medico-legal Cases in Casualty of a Tertiary Care Hospital in Delhi (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
Medico-legal cases are showing rising trend throughout the world. The aim of the present study is to throw light on the profile and pattern of medico-legal cases presenting to casualty department of tertiary care hospital in Delhi. In present study, total number of 2107 medico-legal cases from 1st January 2016 to 30th December 2018 was included. Data was collected from Medico-legal case register in various parameters and was analyzed and discussed. Male predominance was observed in 77.03% cases. Maximum cases reported from the age group of 21–30 years (25.63%) followed by age group of 31–40 years (16.94%). In majority of cases (79.97%), alleged manner of incidence was accident followed by suicide. Majority of cases (70.15%) were of road traffic accident (RTA). Majority of cases (53.30%) reported to casualty within 1 hour from the time of incidence. Such incidences can be prevented by giving awareness through proper education and training of safety standards by administrators through road safety programs
Keywords: Medico-legal cases; Casualty medical officer; Road traffic accident; Casualty